The Potential Benefits of Non-skills Training (Mental Toughness) for Elite Athletes: Coping With the Negative Psychological Effects of the COVID-19 Pandemic - Neil Dagnall; Kenneth Graham Drinkwater; Andrew Denovan; R. Stephen Walsh (Frontiers Media S.A., 2021)
The spread of COVID-19 has had a significant impact on global sport. This is especially true at the elite level, where it has disrupted training and competition. Concomitantly, restrictions have disrupted long-term event planning. Many elite athletes remain unsure when major events will occur and worry about further interruptions. Although some athletes have successfully adapted to the demands of the COVID-19 crisis, many have experienced difficulties adjusting. This has resulted in psychological complications including increased stress, anxiety, and depression. This article critically examines the extent to which non-cognitive skills training, in the form of increased awareness of Mental Toughness, can help elite athletes inoculate against and cope with negative psychological effects arising from the COVID-19 pandemic. Non-cognitive skills encompass intrapersonal (motivations, learning strategies, and self-regulation) and interpersonal (interactions with others) domains not directly affected by intellectual capacity. Previous research indicates that enhancement of these spheres can assist performance and enhance mental well-being. Moreover, it suggests that training in the form of increased awareness of Mental Toughness, can improve the ability to cope with COVID-19 related challenges. In this context, Mental Toughness encompasses a broad set of enabling attributes (i.e., inherent and evolved values, attitudes, emotions, and cognitions). Indeed, academics commonly regard Mental Toughness as a resistance resource that protects against stress. Accordingly, this article advocates the use of the 4/6Cs model of Mental Toughness (i.e., Challenge, Commitment, Control, and Confidence) to counter negative psychological effects arising from COVID-19.